Application of the modified Dubinin-Astakhov equation for a better understanding of high-pressure hydrogen adsorption on activated carbons. (30th September 2020) - Sdanghi, G.; Schaefer, S.; Maranzana, G.; Celzard, A.; Fierro, V.
Abstract: Hydrogen storage in activated carbons (ACs) has proven to be a realistic alternative to compression and liquefaction. Adsorption capacities up to 5.8 wt% have indeed been obtained. The amount of adsorbed hydrogen depends on the textural properties of ACs, such as specific surface area and total pore volume. The modified Dubinin-Astakhov (MDA) equation proved to be a good analytical tool for describing hydrogen adsorption in a wide range of pressures and temperatures and for several adsorbents. The parameters of this model have been found to be somehow related to the textural properties of the adsorbent. Thus, we applied this model to understand better hydrogen adsorption on ACs over a wide range of pressures in relation to the textural properties of the ACs. We applied the MDA equation to evaluate also the isosteric heat of hydrogen adsorption, which was found to be in the range of 5–9 kJ mol −1 . We compared the results obtained by applying the MDA equation with those obtained by both the sorption isosteric method and the Sips equation. This allowed finding the temperature dependence of the isosteric heat of adsorption, as well as its variation with respect to the textural properties of the ACs. Highlights: The modified Dubinin-Astakhov (MDA) equation well described H2 adsorption up to 15 MPa. MDA parameters were related to the textural properties of activated carbons (ACs). Isosteric heats of adsorption in the range 5–9 kJ mol −1 were found. Adsorption entropy was higher for ACs having both narrow pores and high microporosity. c p of the adsorbed phase varied from 10 to 18 J mol −1 K −1 .